Theory of longitudinal recoil-ion momentum distribution in ion-atom ionization - Rodríguez Chariarse, Vladimir Daniel (2005)
The longitudinal recoil-ion momentum distributions of single ionization in collisions between fast heavy ions and atoms are analyzed by exploring the three-body kinematics and its relation to dynamic processes. It is found that there is a kinematic threshold for the longitudinal recoil-ion momentum distributions that can be ascribed to electron capture to the continuum (ECC). The finite cross section at threshold provides unambiguous evidence of the divergence of the ECC peak when the electron velocity is equal to the projectile velocity. Other aspects associated with the ionization process, such as soft-electron emission and binary-encounter collision, are also studied. Theoretical longitudinal recoil-ion momentum distributions are also compared to existing experiments. © 1995 The American Physical Society.